The SAGE handbook of progress in human geography - Lee, Roger 1945-; Castree, Noel 1968- (SAGE, 2012)
This handbook asks the central question, 'What does it mean and what difference does it make to imagine, think and act geographically in the world?' It explores how human geography is essential to the understanding of, and active engagements in, the human and non-human worlds.